1999
DOI: 10.1094/mpmi.1999.12.7.633
|View full text |Cite
|
Sign up to set email alerts
|

An hrcU-Homologous Gene Mutant of Xanthomonas campestris pv. glycines 8ra That Lost Pathogenicity on the Host Plant but Was Able to Elicit the Hypersensitive Response on Nonhosts

Abstract: Transposon mutagenesis was used to isolate nonpathogenic mutants of Xanthomonas campestris pv. glycines 8ra, which causes bacterial pustule disease in soybean. A 6.1-kb DNA region in which a mutation gave loss of pathogenicity was isolated and found to carry six open reading frames (ORFs). Four ORFs had homology with hrcU, hrcV, hrcR, and hrcS genes of Ralstonia solanacearum and X. campestris pv. vesicatoria. One nonpathogenic mutant, X. campestris pv. glycines H80, lost pathogenicity on soybean but was able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
3
1
2
Order By: Relevance
“…While infection with the wild-type strain showed clear disease symptoms including water-soaking, hyperplasy and necrosis, the Δ hrcU strain failed to produce any disease symptoms in the susceptible citrus host. This result is consistent with the absolute requirement for HrcU homologs for the functioning of all T3SS systems [22], [32]. The phenotype of the Δ hrcU strain could be reverted by the expression of wild-type HrcU coded by the pUFR047_ hrcU plasmid or by expression of the HrcU XAC_AAAH coded by the pUFR047_ hrcU AAAH plasmid (Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…While infection with the wild-type strain showed clear disease symptoms including water-soaking, hyperplasy and necrosis, the Δ hrcU strain failed to produce any disease symptoms in the susceptible citrus host. This result is consistent with the absolute requirement for HrcU homologs for the functioning of all T3SS systems [22], [32]. The phenotype of the Δ hrcU strain could be reverted by the expression of wild-type HrcU coded by the pUFR047_ hrcU plasmid or by expression of the HrcU XAC_AAAH coded by the pUFR047_ hrcU AAAH plasmid (Fig.…”
Section: Resultssupporting
confidence: 86%
“…In Xanthomonas campestris pv. glycines 8ra, the HrcU homolog is not required for HR induction on non-host plants, pepper and tomato, or for the multiplication of bacteria in the host plant, but was required for the pathogenic symptoms on soybean [22]. On the other hand, insertion mutagenesis in the Xcv hrpC operon, which codes for both HrcU and HrcV, resulted in nonpathogenic mutants that exhibited significantly reduced growth in pepper leaves and lost the ability to induce HR in resistant host plants and in non-hosts [23].…”
Section: Introductionmentioning
confidence: 99%
“…vesicatoria. First, Oh and colleagues reported that a mutation in hrcU did not abolish the ability to induce HR in pepper plants (34). However, we found that a hrcU mutation did abolish the ability to induce HR in pepper plants.…”
Section: Discussioncontrasting
confidence: 54%
“…Em Xanthomonas campestris pv. glycines 8ra, o homólogo HrcU, não é necessária para a indução de HR em plantas resistentes como pimenta e tomate ou para a multiplicação da bactéria na planta hospedeira, mas é necessária para o desenvolvimento dos sintomas de patogenicidade na soja (Oh et al, 1999). Por outro lado, mutagênese no operon hrpC de Xcv, que codifica para as proteínas HrcU e HrcV, resultou em mutantes não patogênicos que apresentaram uma redução significativa do crescimento da bactéria em folhas de plantas hospedeiras, como a pimenta, e perderam a capacidade de induzir HR em plantas resistentes (Bonas et al, 1991).…”
Section: 1-interações Entre As Proteínas Hrcu E Hrpb2unclassified
“…Por isso, conclui-se que o N263 era indispensável para a autoclivagem de YscU (Riordan e Schneewind, 2008 vesicatoria (Lorenz et al, 2008a (Oh et al, 1999). Curiosamente, entretanto, este ortólogo de hrcU não é necessário para a multiplicação da bactéria na planta hospedeira nem é necessária para a indução de HR em plantas resistentes (Oh et al, 1999). Isso é consistente com nossas observações, embora HrcU é necessária para o desenvolvimento de sintomas de cancro cítrico no hospedeiro, não é necessária para o crescimento bacteriano em plantas suscetíveis.…”
Section: 1-interações Entre As Proteínas Hrcu E Hrpb2unclassified